STUDI EKSPLORATIF TERHADAP LAPORAN HASIL PEMERIKSAAN KABUPATEN/KOTA YANG MEMPEROLEH OPINI WAJAR DENGAN PENGECUALIAN MENGGUNAKAN CONTENT ANALYSIS - Vita Fitria Sari (JURIS (Jurnal Ilmiah Syariah), 2018)
According to BPK (2009), most of the audited financial statements of the Indonesia’s local government have obtained qualified opinion from BPK. It is useful to explore what such accounts that make the reports qualified by BPK. This study aims to exploratory identify in order to know accounts that appear frequently as being qualified by BPK. Such knowledge would be useful for mapping the problems related to the quality of financial reporting of the local governments. Previous research on governmental financial reporting not yet addressed this necessity. Although this study does not go further to explain the reasons for the qualification, the obtained knowledge would help the local government to set policy for enhancing the quality f their financial reporting. Content analysis undertaken explores that the accounts that are frequently qualified from balanced sheet are assets especially current assets, while from the budget realization reports are expenditures especially operating expenditure. The problems inherent in the qualified accounts associated with the criteria of fairness of local government’s financial statements included the incompatibility with government accounting standards in Indonesia, non-compliance with laws and regulations and weaknesses of internal control system. While the insufficiency of disclosure did not became a problem in the qualified accounts on the participant’s financial statements.